Disseminated Trichosporon infection in a renal transplant recipient. Issue 4 (14th July 2015) - Chaitanya, V.; Sangeetha Lakshmi, B.; Venkata Kumar, A.C.; Hari Krishna Reddy, M.; Ram, R.; Siva Kumar, V.
Abstract Trichosporon species are basidiomycetous yeast‐like anamorphic organisms (Basidiomycota, Hymenomycetes, Tremelloidae, Trichosporonales) that are widely distributed in nature. Trichosporon species colonize the skin and gastrointestinal tract of humans. We present a report of disseminated Trichosporon in a renal allograft recipient. Our patient satisfied the definitions of both "proven invasive trichosporonosis" and "probable pulmonary infection." Only 2 reports of disseminated Trichosporon infection in renal transplant recipients, to our knowledge, have been published.